The Impact of Digital Lifestyles on Young People's Health: Social Media Abuse, Physical Inactivity and Psychological Impacts - Lusianawati, Hayu; Sulaeman, Sulaeman; Sianipar, Godlif; Rasmita, Dina (Westscience Press, 2023)
In the digital age, adolescents in DKI Jakarta Province, Indonesia, are experiencing a transformative shift in their lifestyles, characterized by the pervasive influence of digital technologies. This research aimed to comprehensively investigate the multifaceted impact of digital lifestyles on the health of adolescents, with a specific focus on social media abuse, physical inactivity, and psychological well-being. Through a mixed-methods approach encompassing surveys and interviews, data from 500 adolescents were collected and analyzed. The findings revealed that digital lifestyles have become integral to the lives of adolescents, with social media use averaging 3.5 hours per day. However, this extensive use has led to concerning issues, including cyberbullying experiences among 18% of participants and feelings of inadequacy in 42% due to social comparison. Additionally, physical inactivity was prevalent, with only 38% meeting the recommended daily physical activity guidelines. These behaviors were associated with various health implications, such as poor sleep quality and eye strain. Psychological well-being also bore the brunt of digital lifestyles, with 32% of adolescents reporting symptoms of anxiety and 28% experiencing symptoms of depression. Despite these challenges, self-esteem levels remained moderate to high for most participants.